STRATEGI PEMASARAN PT. BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN, TBK TERHADAP PRODUK TABUNGAN BJB TANDAMATA MY FIRST - Debora, (2023)
The business development in the banking industry is expanding, leading to increasingly fierce competition in product marketing. Bank Bjb has a product called Tabungan Tandamata My First, which is aimed at introducing the product to the public, especially children, in order to educate them about starting to learn and cultivate saving habits from an early age. To promote the product, marketing efforts are necessary to introduce it to the public. Marketing activities are inseparable from the implementation of strategies to enhance the quality of these marketing activities. Therefore, a good and attractive marketing strategy is needed to provide information about Tabungan Tandamata My First. The marketing strategy implemented to enhance the Tabungan Tandamata My First product is through the 7P marketing mix. The obstacles faced in marketing the product include lack of awareness, lack of interest among the public and children in saving, and parents' limited literacy regarding the culture of preparing their children's future through saving. The author has a solution that can help overcome these obstacles in marketing activities, which is to conduct socialization campaigns in schools by inviting parents or guardians to educate children about the concept of money from an early age, explaining the importance of preparing their children's future through saving, accompanied by engaging games and attractive rewards.